The influence of physical attributes of surface topographies in relation to marine biofouling - Wong, Felicia Wong Yen Myan (2017)
Solid surfaces that spend long periods of time in aquatic environments are susceptible to the accumulation of marine fouling organisms and this phenomenon is known as marine biofouling. This is a natural process which has significant impacts on marine industries. Research to develop new antifouling solutions focuses on the development of non-toxic solutions that can deter biofouling. A non-toxic antifouling approach that has gained interest in recent years is to modify the surface’s structure to disrupt organism settlement (Kirschner and Brennan 2012; Magin et al. 2010; Myan et al. 2013). Many studies determined that uniform arrays of single layered, micro-topographies are effective at deterring the initial settlement of fouling organisms. In contrast, most studies that tested uniform arrays of single layered, macro-topographies concluded that these topographies are not suitable for antifouling applications. Both single layered, micro-topographies and single layered, macro-topographies were determined to have limitations at mitigating biofouling. This resulted in the interest to develop hierarchical topographies. Hierarchical topographies are surfaces that consist of features that are varied in size and shape. It was suggested that the diverse nature of hierarchical topographies might be able to deter biofouling from a wider array of organisms. This research fabricated and tested a wide range of topographies (uniform, non-uniform, micro, macro, hierarchical, etc.) in a field study. A field study was preferred over lab experiments because results will reflect the antifouling efficacy of the surfaces in a marine environment. These results will indicate the topographies’ viability and future potential for industrial applications. Antifouling efficiency was evaluated by measuring fouling resistance (during the field test) and fouling removal (after the field test) of all topographies. Physical attributes (pattern geometry, pattern size, and surface roughness) of topographies were characterised with Scanning Electron Microscopy (SEM) and Laser Scanning Confocal Microscopy (LSCM). Statistical analysis was carried out to evaluate the significance of the topographies’ physical attributes on the antifouling efficiency of the topographies.